Influence of Exogenous Factors on Genomic Imprinting. 2. Effect of Bad Habits of Parents on Genomic Imprinting of the Descendants - A.E. Abaturov (Zaslavsky O.Yu., 2016)
The article presents research data, which suggest that alcohol abuse and smoking of parents have an adverse effect on fetal development and the health of the child. These factors disrupt the processes of DNA methylation of imprinted genes, causing an increased risk of intrauterine growth retardation, and of pathological abnormalities in fetal neurogenesis.